Asymmetric bilateral hip dislocation in young man: a case report - Giaretta, Stefano; Silvestri, Andrea; Momoli, Alberto; Micheloni, Gian Mario (Acta Biomedica Atenei Parmensis, 2019)
Bilateral hip dislocation is a rare event, asymmetric dislocation is even rarer. Due to the intrinsic stability of the hip joint this lesions usually follow a high energy trauma. Because of the common associated lesions, the initial clinical assessment should be performed thoroughly. CT scan rather than x-rays offers a complete survey of these possible associated injuries such as thoracic or abdominal bleedings, neurologic lesions or fractures directly associated with the hips dislocations. The first goal should be reduction of the dislocation to prevent avascular necrosis (AVN) of the femoral head and arthritis. We report a case of a young man with right anterior hip dislocation and left posterior hip dislocation with associated fracture of the posterior wall.